Child tracking system using GPS and Arduino - Nurul Syafiqah, Zaidi (2019)
Child Tracking System using GPS and Arduino was developed to help parents in monitoring their children and hence, reduce the number of missing child cases in Malaysia. This system will involve the uses of GPS (Global Positioning System), GSM (Global System for Mobile Communication), vibration tilt sensor, and Arduino Uno Microcontroller. In this application, GPS will help to determine coordinates of the child’s location in latitude and longitude with the help of Google maps directly to parents’s smart phone. Then, GSM will send the child’s location to parent’s smart phone via Short Messaging System (SMS). An application will be developed for this project to allow parents to view their child current location using their smart phone. In this project, the vibration tilt sensor which is embedded in the child’s smart watch will detect the shaking or struggle of their child to ensure the safety of the child. The vibration tilt sensor will measure the bandwidth of vibration and send shaking’s signal to Arduino Uno Microcontroller. Then, the Arduino Uno Microcontroller will send alert message to Parent according to the amount of bandwidth of shaking’s signal received from vibration tilt sensor. Hence, the parent would be notified by the condition of their child whether they are safe or not. The methodology used in this project development is using Rapid Application Development (RAD). This Child Tracking System will be developed by using the mobile application systems that need to be installed by the user especially parents and it will be connected to the prototype of smart watch for child.